2022
DOI: 10.1109/access.2022.3166901
|View full text |Cite
|
Sign up to set email alerts
|

Novel Meta-Heuristic Algorithm for Feature Selection, Unconstrained Functions and Engineering Problems

Abstract: This paper proposes a Sine Cosine hybrid optimization algorithm with Modified Whale Optimization Algorithm (SCMWOA). The goal is to leverage the strengths of WOA and SCA to solve problems with continuous and binary decision variables. The SCMWOA algorithm is first tested on nineteen datasets from the UCI Machine Learning Repository with different number attributes, instances, and classes for feature selection. It is then employed to solve several benchmark functions and classical engineering case studies. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…This proposal consists in a two-stream architecture to combine the RGB and the skeleton data from videos. In their work, authors in [34] presented the Spatial Temporal Graph Deconvolutional Network (ST-GDN). This model aims to alleviate the noise propagated across the node messages of the skeleton graph by using a deconvolution layer as a filter.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This proposal consists in a two-stream architecture to combine the RGB and the skeleton data from videos. In their work, authors in [34] presented the Spatial Temporal Graph Deconvolutional Network (ST-GDN). This model aims to alleviate the noise propagated across the node messages of the skeleton graph by using a deconvolution layer as a filter.…”
Section: Related Workmentioning
confidence: 99%
“…Table 2: NTU-RGB+D accuracy results. In the table, 50% st and 80% st correspond to the results obtained using the bp-50 and bp-80 subsets, respectively Method X-View X-Sub ST-GCN [8] 81.5% 88.3% AM-STGCN [20] 83.34% 91.4% 2s-AGCN [33] 88.8% 95.1% ST-GDN [34] 89 Finally, we have found that the bottom-up approach with PAFs used by OpenPose makes it ideal in use-cases where multiple persons are interacting with each other in a particular action. However, this system is not as portable as the BlazePose system and it requires a considerable computation capacity to operate.…”
Section: Ntu-rgb+dmentioning
confidence: 99%
“…DTO plays a crucial role in enhancing the performance of MLP by suppressing or strengthening the weights of the neural network. MLP is a nonlinear machine learning technique that is particularly useful in the detection phase since it is a stable, robust classifier with high detection accuracy [38]. Throughout the lifespan of the MANET, the proposed approach will be performed at regular intervals.…”
Section: Proposed Approachmentioning
confidence: 99%
“…The dataset contains a wide range of characteristics, both in size and unit. Data integrity may be maintained throughout the time when scaled [33][34][35][36][37][38][39][40]. As part of data preparation, the amount of samples in the dataset is balanced such that each class has equal numbers of samples [41][42][43][44][45][46][47].…”
Section: Dataset Preprocessingmentioning
confidence: 99%